Biosorption of Cu (II) for Biomass containing Pectin - Villanueva H., Claudia (2005)
The adsorption of Cu (II) has been investigated for treated biomasses of orange shells, lemon shells and nopal, which contain pectin in its composition. The dry and crushed biomass was treated with NaOH, which produces the desmetoxilation of the pectin, later was treated with a solution 0,2 M of CaCl2, which allows improving the mechanical stability of the biomasses. The good pH in the process of bioadsorción of the Cu (II) was in the range of 4 - 4,5. The capacity biosorption these biomasses is evaluated in batch. The biosorption isotherms are described by the models of Langmuir and Freundlich. According to the pattern of Langmuir, the maximum capacities of adsorption (qmáx) of the treated biomasses were: shell of orange 36,23 mg/g, lemon 46,95 mg/g and nopal 44,25 mg/g.